THE LAW OF GRADUATION IN LINGUISTICS - Aziza Shavkatovna Qurbonmuradova (European Science Publishing, 2024)
Studying the phenomenon of gradation in the semantic relations of language units on the basis of modern paradigms. The phenomenon of gradation existing in synonymy and antonymy creates the opportunity to distinguish and research other lexical-semantic relations. The fact that gradation is of special importance in the semantic relations of language units will be clarified by the researches of the next period of linguistics. The manifestation of gradation in linguistic phenomena refers to the investigation of its relationship with other lexical-semantic paradigms, scientific approaches about graduonymic relationship.
Keywords: Level status, lexical-semantic relationship, synonymy and antonymy, level category, phenomenon of graduanimy.